Does foreign direct investment affect wage inequality? An empirical investigation - Paolo Figini; Holger Görg (Institute for the Study of Labor (IZA), 2006)
We use a panel of more than 100 countries for the period 1980 to 2002 to analyse the relationship between inward foreign direct investment (FDI) and wage inequality. We particularly check whether this relationship is non-linear, in line with a theoretical discussion. We find that the effect of FDI differs according to the level of development: we depict two different patterns, one for OECD (developed) and one for non-OECD (developing) countries. Results suggest the presence of a non linear effect in developing countries; wage inequality increases with FDI inward stock but this effect diminishes with further increases in FDI. For developed countries, wage inequality decreases with FDI inward stock and there is no robust evidence to show that this effect is non-linear.
Keywords: 330